Aspects of calculation of resistance vapor penetration of enclosing structures - Yurin, Oleg; Mahas, Nataliia; Zyhun, Alina; Musiienko, Olha (Academic journal Industrial Machine Building Civil Engineering, 2020)
When determining the resistance to vapor penetration of the vapor barrier layer which is based on the zero balance of moisture accumulation per year and the value of the allowable increase in moisture content of the material during the period of moisture accumulation. The temperature and relative humidity of the outside air for the period of the three coldest months of the heating period or the period with average monthly negative temperatures are usually used in the calculations. Although, the duration of the moisture accumulation period may not coincide with this period, and the value of the resistance to vapor penetration of the vapor insulation in the enclosing structures may not be determined correctly. The clarification of the calculation methodology was suggested. It is necessary to determine the months, when moisture accumulation occurs in the insulation of the enclosing structure, after determining the average temperature and relative humidity of the outside air during these months and calculate the resistance to vapor penetration of the vapor insulation layer.